2011
DOI: 10.1039/c0cp02494e
|View full text |Cite
|
Sign up to set email alerts
|

2D assembly of gold–PNIPAM core–shell nanocrystals

Abstract: 2D arrays of Au-PNIPAM core-shell nanocrystals were fabricated using convective deposition and spin-coating. The particle density and ordering were studied by AFM. Annealing at 700 °C removes the polymer shell, while retaining a monolayer of well-separated gold nanoparticles. The surface plasmon modes of the colloid monolayers could be measured by spectroscopic ellipsometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 26 publications
1
57
0
Order By: Relevance
“…Reproduced with permission 10, 11, 12, 18, 20, 21, 79, 120, 133, 135, 138, 144, 171, 172, 173, 174, 175, 176, 177. Copyright 1998, 2001, 2006, 2007, 2009, 2010, 2011, 2013, Nature Publishing Group.…”
Section: Introductionmentioning
confidence: 99%
“…Reproduced with permission 10, 11, 12, 18, 20, 21, 79, 120, 133, 135, 138, 144, 171, 172, 173, 174, 175, 176, 177. Copyright 1998, 2001, 2006, 2007, 2009, 2010, 2011, 2013, Nature Publishing Group.…”
Section: Introductionmentioning
confidence: 99%
“…This could be used to determine the molar mass of the overall hybrid particles simply from absorbance measurements. In a different work, Mulvaney et al [62] have shown that the control over the shell thickness of gold-poly-(NIPAM) microgels can be used in the preparation of particle monolayers with different intercore separation distances. In this work, the authors employed different deposition techniques to produce self-assembled monolayers of the core-shell particles and studied the surface coverage and core-to-core distance.…”
Section: Plasmonic Hybridsmentioning
confidence: 98%
“…Once the substrate is covered with colloidal particles with specific inter-particle spacing, surface coverage determines the optical properties, that is, absorption, scattering and transmission [132][133][134][135]. Whereas a low area fraction f area of only a few percent will only have negligible influence, a high area fraction will for example significantly lower the transmission through this layer.…”
Section: Particle Functionalizationmentioning
confidence: 99%